The rise of young voters: Making up a fifth of eligible voters, young Malaysians are a crucial source of support in GE13 - The Edge, Financial Daily (The Edge Financial Daily, 2013)
Prime Minister Datuk Seri Najib Razak escaped a direct showdown with youth when a 23-year-old student gave up his bid to challenge him in his home constituency in the May 5 general election.